2014
DOI: 10.1016/j.devcel.2014.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Osterix Marks Distinct Waves of Primitive and Definitive Stromal Progenitors during Bone Marrow Development

Abstract: Mesenchymal stem and progenitor cells (MSPCs) contribute to bone marrow (BM) homeostasis by generating multiple types of stromal cells. MSPCs can be labeled in the adult BM by Nestin-GFP, whereas committed osteoblast progenitors are marked by Osterix expression. However, the developmental origin and hierarchical relationship of stromal cells remain largely unknown. Here, using a lineage-tracing system, we describe three distinct waves of contributions of Osterix+ cells in the BM. First, Osterix+ progenitors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

34
472
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 387 publications
(515 citation statements)
references
References 43 publications
34
472
3
Order By: Relevance
“…Lineage tracing with Axin2, a Wnt target gene, initiated at the neonatal stage, showed that the Wnt-responding population contained stromal cells that were able to robustly contribute to bone development, maintenance, and injury repair over the long term. The in vivo fate and longevity of the Axin2-labeled population is similar to those observed from the lineage traces using Osx-CreERT (20,21), suggesting significant overlap in the Wntresponding and Osx-expressing stromal populations during the neonatal stage, both of which contain progenitors that contribute to the osteolineage over the long term.…”
Section: Wnt-responding Stromal Population Contains Long-lived Osteolsupporting
confidence: 53%
See 4 more Smart Citations
“…Lineage tracing with Axin2, a Wnt target gene, initiated at the neonatal stage, showed that the Wnt-responding population contained stromal cells that were able to robustly contribute to bone development, maintenance, and injury repair over the long term. The in vivo fate and longevity of the Axin2-labeled population is similar to those observed from the lineage traces using Osx-CreERT (20,21), suggesting significant overlap in the Wntresponding and Osx-expressing stromal populations during the neonatal stage, both of which contain progenitors that contribute to the osteolineage over the long term.…”
Section: Wnt-responding Stromal Population Contains Long-lived Osteolsupporting
confidence: 53%
“…As the Osx population has been shown to contain long-lived stromal progenitors that support osteogenesis (20,21), our observation of the overlap in Axin2 and Osx expression (Fig. 1 B-D) prompted us to ask if the Axin2-expressing population contains osteolineage progenitors.…”
Section: Neonatal Wnt-responding Stromal Population Contains Progenitorsmentioning
confidence: 99%
See 3 more Smart Citations